Microhabitat and plant structure of Compsopogon coeruleus (Compsopogonaceae, Rhodophyta) populations in streams from São Paulo State, southeastern Brazil - Necchi, O.; Branco, CCZ; Gomes, RRV (Elsevier B.V., 1999)
Microhabitat distribution was investigated in three populations of C. coeruleus to determine the distributional patterns and their controlling factors, as well as morphometric adaptations to varying conditions on a scale of a few centimetres. Morphometric variations and their relations with physical variables (current velocity, irradiance, depth and type of substratum) revealed some particular characteristics for each population and indicate particular adaptations. However, some trends were clear: 1) larger plants (length and/or diameter) produced a higher quantity of monosporangia in the three populations; 2) plant length and diameter were positively correlated in two populations; 3) plant diameter was positively correlated with current velocity in two populations; 4) higher percent cover was associated with substrata composed of macrophytes in two populations. C. coeruleus occurred under relatively wide microhabitat conditions and had high niche width values, suggesting a tolerance to considerable variation in physical variables. These characteristics contribute to the species' wide distribution in Brazilian streams, both spatial (at distinct scales) and seasonal. (C) ADAC / Elsevier, Paris.
Keywords: compsopogon; current velocity; freshwater red algae; microhabitat; plant structure; Rhodophyta; stream